Alopecia Areata: Etiopathogenesis, Diagnostics and Treatment – A Literature Review - Oleksińska, Karolina; Pracoń, Karolina; Pietrzak, Maria; Łupina-Romaniuk, Marcela; Kołodziejczyk, Julia; Chawryło, Aneta; Piecuch, Dominika; Świetlicka, Gabriela; Pietraś, Paulina; Stolarczyk, Michał (Quality in Sport, 2026)
Background. Alopecia areata is an autoimmune disease affecting approximately 2% of the global population. It is characterized by non-scarring hair-loss and is closely linked to severe mental health issues and other allergic or autoimmune diseases. Aim. The aim of this review is to summarize epidemiology, pathophysiology, diagnostics and treatment in Alopecia Areata. Material and methods. This literature review includes articles from PubMed and publishers’ websites. The selection criteria specifically targeted clinical and scientific data published from the year 1995 onward, focusing on the management and characteristics of patients diagnosed with alopecia areata. Results. The review demonstrates that Alopecia areata is driven by inflammatory response. Diagnostic approaches must include screening for other medical conditions and use trichoscopy to assess disease activity.. Conclusions. Alopecia areata requires an early and individualized approach that addresses both physical hair loss and psychiatric comorbidities. Modern targeted therapies offer results for severe cases, though future long-term clinical trials are necessary to establish standardized dosing regimens and minimize relapse rates after treatment discontinuation.